2023
DOI: 10.32996/jeltal.2023.5.4.12
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated Instruction as Strategy in Improving Reading Comprehension

Amalia Potot,
Louie Nikki Kyamko,
Raiza Rhea Reponte-Sereño
et al.

Abstract: Reading and understanding what was read are integral parts in the life of every individual and are indispensable in the circle of educational system. However, this vital skill is what most students lack interest of. As a result, it affects their understanding in the other areas of their education endeavor. To address the problem, Robert Glaser proposed a strategy, the so called Individually Prescribed Instruction [IPI], which later on was known as Differentiated Instruction. It showcases a variety of classroom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Students with special educational needs can develop skills to achieve instructional goals. Studies have reported positive effects of differentiated instruction on students' performance in reading fluency and comprehension (Baumgartner, Lipowski, & Rush, 2003;Potot et al, 2023). For this to occur, it is necessary to adapt the learning environment, content, process, and outcomes, taking into account the heterogeneous nature of the classroom rather than teaching all students uniformly (Sousa &Tomlinson, 2011).…”
Section: Differentiated Instructionmentioning
confidence: 99%
“…Students with special educational needs can develop skills to achieve instructional goals. Studies have reported positive effects of differentiated instruction on students' performance in reading fluency and comprehension (Baumgartner, Lipowski, & Rush, 2003;Potot et al, 2023). For this to occur, it is necessary to adapt the learning environment, content, process, and outcomes, taking into account the heterogeneous nature of the classroom rather than teaching all students uniformly (Sousa &Tomlinson, 2011).…”
Section: Differentiated Instructionmentioning
confidence: 99%